Percepção da doença e adesão ao tratamento em um grupo de pacientes com hipotireoidismo - Souza, Silvia Patrícia Alves de (2014)
BACKGROUND. Hypothyroidism is the most common thyroid disease. Mostly, the treatment consists in the thyroid hormone replacement throughout the lifetime of the patient. In this context, therapeutic success depends largely on patient adherence to treatment, and the illness perception is important determinant of behavior that will be issued to the management of the disease. PURPOSE. Understand the illness perception in patients with hypothyroidism and its influence on medication adherence. METHODS. The study has a cross-sectional design and was conducted in the endocrinology clinic of the University Hospital of the Federal University of Sergipe. One hundred and eighty-five patients with a diagnosis of primary hypothyroidism and use of levothyroxine for at least two months were interviewed with regard to socio-demographic and clinical data, perception of hypothyroidism and medication adherence behaviors. To this end, the following instruments were used: socio-demographic and clinical questionnaire, adapted and validated for the Brazilian culture version of Brief Illness Perception Questionnaire and Therapeutic Adherence Scale Morisky. RESULTS. Most patients were female (94.6%) and had lower education (4.9% were illiterate and 48.6% had incomplete primary education) . Their ages ranged from 25 to 79 years, with a mean of 50.8 (SD = 12.1) years. The non-adherence rate obtained was 42.2%, and 34.6% of patients reported unintentional adherence, 4.3% intentional adherence and 3.2% both types of behaviour. It was also found that 26.5% of patients had serum levels of thyroid-stimulating hormone outside the reference range, lying high in 17.3% of patients and 9.2% of them deleted. Furthermore, there was a statistically significant relationship between hormone and medication adherence (p = 0,002). Regarding the illness perception, it was found that patients who reported medication adherence had significantly lower scores in relation to the consequences (p = 0.048), concern (p = 0.046) and emotions (p = 0.019) compared with patients who did not adhere to treatment. CONCLUSION. The high prevalence of non-adherence and the influence of some components of illness perception demonstrated in this study suggest the need for strategies based on knowledge of the illness perceptions of the patient to improve adherence to treatment of hypothyroidism.